Kekuatan Putusan Badan Penyelesaian Sengketa Konsumen Terkait Keberatan dan Pembatalan Putusan Arbitrase Sebagai Alternative Dispute Resolution dalam Penyelesaian Sengketa Konsumen - Surya Muhammad Gunarsa (Faculty of Law, Universitas Pattimura, 2019)
Consumer dispute can be resolved by litigation and non-litigation based on agreement of the parties. Presence of the Consumer Dispute Resolution Agency (BPSK) considered as a new hope for parties because thats’s give an option to resolve consumer dispute, through BPSK it is expected that dispute can be resolved in a simple, fast, and low-cost manner. However, in fact the verdict issued by BPSK has the disadvantage of not having specificity, it caused by the article 54 point 3 of Consumer Protection Law mention that the BPSK decision is final and binding but can still be submitted for objection, even cancellation, then the absence of executorial power on the BPSK decision causes this BPSK decision to have no merit.